Alginate-coated chitosan nanoparticles for pH-dependent release of tamoxifen citrate. Issue 1 (31st December 2022) - Waqas, Muhammad Khurram; Safdar, Shees; Buabeid, Manal; Ashames, Akram; Akhtar, Muhammad; Murtaza, Ghulam
Abstract: Chitosan-based nano-sized particles increase the penetration of the drug through the narrow junction into the bloodstream and target the specific site. The objective of this study was to prepare chitosan nanoparticles to entrap a hydrophobic drug (tamoxifen citrate), followed by the alginate coating of the developed nanoparticles to decrease their degradation in the acidic pH. Drug-loaded chitosan nanoparticles were prepared by the ionic gelation method. Alginate coating was done by dissolving sodium alginate to buffer solution and drug-loaded chitosan nanoparticles drop-wise under mild agitation. The size of alginate coated chitosan nanoparticles, zeta potential, surface morphology, in-vitro drug release, and entrapment efficiency was measured. The optimised formulation of both uncoated (SH3) and coated (SH7) formulation showed the particle size, PDI, and zeta potential with values 221 & 338 nm, 0.161 & 0.230 and 36.5 & −20.7 mV, respectively. The resulted nanoparticle surface was non-porous. The percentage yield of the optimised formulation SH3 was 28% and SH6 was 33%. The entrapment efficiency of the optimised formulation SH3 (uncoated formulation) and SH6 (coated formulation) is 69.5 and 58.51%, respectively. Chitosan nanoparticles were successfully prepared to entrap tamoxifen citrate. The coating of chitosan nanoparticles decreased their degradation in the acidic pH.